Providing Preliminary Evidence in the Proofing Process of Rape Cases: Study of Article 52 of Aceh Qanun No.6/2014 Regarding Jinayat Law [Kewajiban Menyertakan Bukti Pemula oleh Korban dalam Proses Pembuktian Kasus Pemerkosaan: Studi Pasal 52 Qanun Aceh Nomor 6 Tahun 2014 Tentang Hukum Jinayat] - Meri Andani (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2020)
Abstract: There is a problem in the case of rape victims who are obliged to include preliminary evidence when filing a complaint against a finger in Article 52 paragraphs 1 and 2 of the Jinayat Law. This article indicates that there is a double burden on women victims of rape because they are not only the targets of horrific crimes but also have to bear the burden of providing preliminary evidence. If the initial evidence is charged to the victim, it will burden and weaken women as victims to reveal the perpetrators of rape. So that the more difficult it is to prove the crime of rape, the more cases of rape and sexual violence against women will increase. Based on the records of the National Commission on Violence Against Women (KOMNAS Perempuan), it appears that violence against women in 2018 in the 2019 annual record (CATAHU) has increased by 406,178 cases, an increase of around 14% compared to the previous year (CATAHU 2018) which was 348,446. Abstrak: Terdapat permasalahan dalam hal korban pemerkosaan yang berkewajiban menyertakan alat bukti permulaan saat mengadukan suatu jarimah di dalam Pasal 52 ayat 1 dan 2 Qanun Hukum Jinayat. Pasal ini mengindikasikan adanya beban ganda pada perempuan korban pemerkosaan karena mereka tidak hanya menjadi sasaran kejahatan yang mengerikan, namun juga harus menanggung beban menyertakan alat bukti permulaan. Jika bukti permulaan dibebankan kepada korban maka memberatkan dan melemahkan kaum perempuan sebagai korban untuk mengungkap pelaku pemerkosaan. Sehingga Semakin sulitnya membuktikan tindak pidana pemerkosaan maka akan semakin meningkatnya kasus pemerkosaan dan kekerasan seksual terhadap perempuan. Berdasarkan catatan komisi nasional anti kekerasan terhadap perempuan (KOMNAS perempuan), tampak kekerasan terhadap Perempuan di tahun 2018 dalam catatan tahunan (CATAHU) 2019 mengalami peningkatan yaitu sebesar 406.178 kasus naik sekitar 14% dibandingkan dengan tahun sebelumnya (CATAHU 2018) yaitu sebesar 348.446.